Storage of vacuum-packaged smoked bologna sausage prepared from Nile tilapia - Bartolomeu, Dayse Aline Ferreira Silva; Waszczynskyj, Nina; Kirschnik, Peter Gaberz; Dallabona, Bruna Rafaela; Costa, Fernanda Janaína Oliveira Gomes da; Leivas, Carolina Lopes (Acta Scientiarum. Technology, 2014)
Changes in smoked bologna sausage manufactured with Niletilapia (Oreochromis niloticus), and wheat fibers in refrigerated storage (6 ± 2°C) during 30 days were evaluated. Minced fish (MF) obtained from waste (parings from the filleting fish operations) of Nile tilapia (Oreochromis niloticus) was used as raw material. In this experiment, were determined Staphylococcus count, the detection of Salmonella sp. (day 0), psychrotrophic count, total and fecal coliforms at45°C, the acceptance sensory test (days 0 and 30), water activity, instrumental color, pH and lipid oxidation analysis (Thiobarbituric acid reactive substances - TBARS) days 0, 5, 10, 15, 20, 25 and 30 of storage. Lipid oxidation (TBARS) and water activity provided significant differences among storage days. However it was concluded that the bologna sausage remained stable and with acceptable quality for 30 days of storage may be a new alternative to adding value to fish products, because the researched microorganisms had a low count, changes in pH were not significant and sensory test indicated good acceptance of the product during the 30 days of storage.